(untitled) (Architecture Image Studies, 2021)
This text offers a writerly experiment aimed at developing a possible method of critical speculative fiction. The subject is an imaginary island modelled on the Cycladic island of Amorgos, Greece, which is depicted here as an all-encompassing design project driven by technologically advanced commercial machinations. The resulting fragments of speculative fiction blur the distinction between manmade and natural, architecture and landscape, commerce and myth. In doing so, the text offers a mode of writing heavy on mediated images populated by speculative subjectivities, while avoiding presenting an overtly critical stance. As such, it casts itself as a writerly equivalent of certain traditions in speculative architectural drawing.